The Foreign and Security Policies of the European Union - Anand Menon (Romanian Journal of European Affairs, 2003)
In only a decade the European Union has moved from being a new kid on the block in terms of foreign and security policies to being a high profile and surprisingly effective international actor. Certainly, it has failed to match the ambitions of some of its most enthusiastic proponents. Certainly, too, European publics know next to nothing about what the Union does in the international realm. It is because of this that, despite their potential and their effectiveness to date, EU policies in this sphere were widely derided as failures following the moment when the attacks of 11 September 2001 shook the western world to its core. The Convention on the Future of Europe and subsequent intergovernmental conference look set to make significant institutional changes to the Union’s foreign and security policy systems. In undertaking these reforms, Convention members, and national governments are doubtless motivated by the laudable objective of enabling the Union to do more on the international stage. One can only hope that these motives notwithstanding, they do not simply propose reforms for their own sake and, in the process, undermine a system that, to the surprise of many, has continued to function respectably in an ever more complex and ever more dangerous world.